Productive entry of foot-and-mouth disease virus via macropinocytosis independent of phosphatidylinositol 3-kinase - Han, Shi-Chong (2018)
Virus entry is an attractive target for therapeutic intervention. Here, using a combination of electron microscopy, immunofluorescence assay, siRNA interference, specific pharmacological inhibitors, and dominant negative mutation, we demonstrated that the entry of foot-and-mouth disease virus (FMDV) triggered a substantial amount of plasma membrane ruffling. We also found that the internalization of FMDV induced a robust increase in fluid-phase uptake, and virions internalized within macropinosomes colocalized with phase uptake marker dextran. During this stage, the Rac1-Pak1 signaling pathway was activated. After specific inhibition on actin, Na+/H+ exchanger, receptor tyrosine kinase, Rac1, Pak1, myosin II, and protein kinase C, the entry and infection of FMDV significantly decreased. However, inhibition of phosphatidylinositol 3-kinase (PI3K) did not reduce FMDV internalization but increased the viral entry and infection to a certain extent, implying that FMDV entry did not require PI3K activity. Results showed that internalization of FMDV exhibited the main hallmarks of macropinocytosis. Moreover, intracellular trafficking of FMDV involves EEA1/Rab5-positive vesicles. The present study demonstrated macropinocytosis as another endocytic pathway apart from the clathrin-mediated pathway. The findings greatly expand our understanding of the molecular mechanisms of FMDV entry into cells, as well as provide potential insights into the entry mechanisms of other picornaviruses.